461. SURGICAL TREATMENT OF STAGE IV ESOPHAGEAL CANCER AFTER CCRT IMPROVES SURVIVAL. (24th September 2022) - Wang, Hu-lin Christina; Chen, Ke-Cheng; Cheng, Chia-Hsien; Wu, Ming-Shiang; Lee, Yi-Chia; Wang, Hsiu-Po; Liou, Jyh-Ming; Kuo, Yu-Ting; Han, Ming-Lun; Chen, Chien-Chuan; Huang, Pei-Ming; Hsu, Hsao-Hsun; et al.
Abstract: Treatment of stage IV esophageal cancer is traditionally palliative, but treatment response is usually poor. The role of surgery in the treatment of advanced esophageal cancer remains controversial. We sought to determine whether surgical treatment followed by neoadjuvant chemoradiation therapy might provide survival benefits for these patients. A retrospective review of 163 esophageal cancer patients with M1 disease (distant organ metastasis) treated at a tertiary medical center hospital was performed from April 2002 to June 2021. Patient demographics and cancer staging, treatment, and disease recurrence, and time of follow up were included for analysis. Univariate and multivariate analysis was performed for overall survival and progression-free survival analysis. Propensity score matching based on patient age and tumor staging characteristics was also performed for analysis. 124 patients were treated by CCRT alone and 39 treated by CCRT plus surgery. 3-year and 5-year progression free survival was 17.7% and 8.9% for CCRT+surgery group vs 0.8% and 0.0% in CCRT only group. (p = 0.019) 3- and 5-year survival was 24.0% and 12.0% in CCRT plus surgery group compared to 2.8% and 1.4% for CCRT only group (p = 0.009). Propensity matching of 39 CCRT plus surgery patients and 78 CCRT-only patients showed similar results (17.5% & 8.5% PFS vs 1.3% & 0.0% for PFS, 24.0% and 12.0% vs 3.9% and 1.9% OS). Surgical resection following CCRT treatment may improve progression-free survival and overall survival for selected patients of esophageal cancer with M1 disease. Surgical indication should be judicious, and further follow up studies should be performed.